Women and Strengthening the Family Economy in the Digital Era in the Development of MSMEs in Yogyakarta - Sulistyaningsih, Sulistyaningsih; Muryani, Tri (TEMALI : Jurnal Pembangunan Sosial, 2024)
This research focuses on how women contribute to strengthening the economy to realize family economic resilience. This kind of phenomenon is also experienced by families in rural areas in Bantul, Yogyakarta. The researcher took a social setting in Babadan Hamlet, Sitimulyo, Piyungan, Bantul, Yogyakarta. This research uses a participatory method with the type PAR (Participatory Action Research). Participatory Research Method is carried out jointly and based on emancipatory-participatory logic. In this research, the community is the research subject involving 15 sources from MSME business actors in interviews and FGDs. The research results show that women in Babadan Hamlet, Sitimulyo of Bantul Regency, Yogyakarta, Indonesia, have an important role in strengthening the family economy. Strengthening the family economy is carried out through various activities ranging from opening a shop business or opening services. However, only 20% of business actors utilize digital media such as WhatsApp, Facebook and Instagram. Meanwhile, the marketplace has not been fully utilized. Apart from that, MSME business actors in Babadan Hamlet, Sitimulyo, Bantul Regency are also not optimal in carrying out product branding. This paper contributes to empirical studies on the importance of women’s role in strengthening the family economy.